Alterações registrais decorrentes da transexualidade: análise jurisprudencial e considerações referentes ao discurso fundamentador das decisões alicerçado na busca da certeza biológica e em normas assecuratórias da dignidade da pessoa humana - Boyadjian, Gustavo Henrique Velasco (2019)
In 2018, in Brazil, the Federal Supreme Court (Supremo Tribunal Federal - STF) assessed the Direct Unconstitutionality Action 4275, which questioned the restrictions on name and gender changes of transgender persons in the civil registry. Until this action, all the rectifications required judicial measures and there was no consensus in the judgments, and there were disagreements that ranged from the competence of the organs to which the requests would be addressed to the acceptance or not of the claim itself. This research presented and discussed elements that supported the favorable decisions and those that denying the judicial request in judgments realized by the Supreme Federal Court (Supremo Tribunal Federal - STF), Superior Court of Justice (Superior Tribunal de Justiça - STJ) and each of the State Courts of the country between 2007 and 2017, including the ADI 4275, according to the search criteria used. The research was structured in two papers. The title of the first is “Investigating the Courts: jurisprudential analysis on the pretensions of name change and sexual reassignment in Brazil between 2007 and 2017”. The second paper is entitled “A Matter of Law: The Recognition of the Self-Definition of Gender Identity by the Brazilian Supreme Court”. In these papers we have argued that the uncertainty or certainty legal about whether or not to obtain the positive outcome of the demand presented, not only kept transgender people in a precarious situation with respect to their recognition, but mainly demonstrated how the name remained tied to name-obligation and name-duty of police, in Brazil, although theoretically the name thesis was adopted as personality right. We also inquire about the displacement of the founding arguments of decisions, which gradually move away from medical knowledge towards the field of human rights.